An Independent and Dignified Criminal Justice System: The Path Toward Substantive Justice - Rahayuningsih, Uut; Sunariyo, Sunariyo; Hamid, Muhammad Qodri; Fajar, Ira Fadia (Dinasti Research, 2025)
The enforcement of criminal law in Indonesia plays a vital role in realizing a state based on law, as mandated by the 1945 Constitution. However, the criminal justice system, which should operate independently and with authority, still faces various serious challenges—ranging from political power intervention, unequal access to justice, to the weak integrity of law enforcement officials. This study aims to analyze the structure and dynamics of Indonesia’s criminal justice system within the framework of national legal politics, using a socio-legal approach that combines normative analysis and empirical field data. The main focus is directed at the integration of three aspects of the legal system: substance (legislation), structure (law enforcement institutions), and legal culture (awareness and behavior of both society and legal officials).The findings reveal that synchronization among the sub-systems of the criminal justice system—namely the police, prosecution, courts, and correctional institutions—is still suboptimal. This is exacerbated by low public trust in law enforcement, the criminalization of vulnerable groups, and the dominance of a formalistic approach that neglects substantive justice. In this context, progressive legal theory becomes highly relevant as a foundation for reforming the criminal justice system toward one that is more humane, just, and people-centered. Improving the quality of human resources in law enforcement is needed through legal education that is not only oriented toward legal certainty but also instills the values of justice and social utility. Therefore, an independent and dignified criminal justice system can only be realized if all legal elements work in an integrated manner and place substantive justice as the main orientation in every law enforcement process.